(untitled) (Research, Society and Development, 2020)
The objective was to understand what the health professionals of a UPA / 24horas Emergency Care Unit know about closed loop communication and the blue code when attending emergency situations. Present a Standard Operating Procedure designed to guide the implementation of closed loop communication and the blue code in responding to emergency situations. This is a strategic action research with 24 health professionals from a emergency care unit in Rio Grande do Sul, Brazil. The data collected between April and October in 2019, through semi-structured interviews and awareness workshops, were submitted to content analysis. As a result, four categories emerged about the (Un) Knowledge of the blue code and closed loop communication; Blue code and closed loop communication at the UPA: perception of its Implementation, as well as Strategies for implementing a Standard Operating Procedure in the emergency. The Standard Operating Procedure was developed for the investigated reality. It is concluded that the Standard Operating Procedure may assist professionals during their performance, which will have a better impact on people in emergency situations.